Pengaruh Umur Panen Pinus Hutan Tanaman terhadap Kualitas Kayu Pertukangan Effect of Harvesting Age of Pine from Forest Plantation on Quality of Wood Construction Materials - Nurwati Hadjib; Osly Rachman (Jurnal Ilmu dan Teknologi Kayu Tropis, 2009)
Research on some properties of wood Pine (Pinus merkusii Jungh et de Vriese) to determine technical rotation for wood construction materials matched to the technical requirements. Pine wood investigated originated from KPH Sukabumi, West Java, from site index III and age of 17, 21, 23, 27 and 28 years. The results showed that morphology, diameter at breast height (DBH), sawing recovery, volume, veneer recovery and bonding strength were not significantly different at 95% confidence level. DBH and cylindricity tend to increase from age of 17 years until 27 years and decrease at 28 years in parabolic. The maximum DBH reach at 25 years, while cylindricity at 26 years. The sawing recovery tends to increase from 17 to 21 years, decrease at 23 years and increase at 27 years. Screw withdrawal resistance of five age level wood tested were significantly different. The relationship between age and wood properties tested tends to the same pattern, paraboloid, while volume and veneer recovery were linear. Differentiated of these equation showed that maximum DBH reach at age of 25, sawing recovery 28 years, maximum density and screw withdrawal resistance at 23 years, bonding strength and wettability at 22 years. Based on its machining properties, wood from 17-21 years belong to class II, and class I for 23 ~ 28 years.